STRUCTURAL AND CONTENT REFORM OF DISTANCE SELLING RULES - Mićović, Andrej; Mihajlovic, Borko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The subject of the article are the rules on distance selling contained in the newly adopted Directive 2023/2673. Until the adoption of Directive 2023/2673, distance selling was regulated by the Directive 2011/83 on consumer rights and Directive 2002/65 concerning the distance marketing of consumer financial services. In order to raise the level of consumer protection and avoid unnecessary overlaps, the scope of application of Directive 2011/83 is extended to contracts on financial services, while Directive 2002/65 is repealed. Amended Directive 2011/83 introduced a separate chapter with rules that apply only to financial services contracts concluded at a distance. Content changes and amedments of the rules on the distance contracts for consumer financial services are related to the trader’s obligations to provide pre-contractual information and explanations, the consumer’s right to withdraw from the contract and the unfair business practices regarding the use of the online interface. Keywords: financial services, information, withdrawal, explanations, consumer, distance selling.